2010
DOI: 10.1088/0004-637x/725/2/1393
|View full text |Cite
|
Sign up to set email alerts
|

THEKEPLERLIGHT CURVE OF V344 Lyrae: CONSTRAINING THE THERMAL-VISCOUS LIMIT CYCLE INSTABILITY

Abstract: We present time-dependent modeling based on the accretion disk limit cycle model for a 270 d light curve of the short-period SU UMa-type dwarf nova V344 Lyr taken by Kepler. The unprecedented precision and cadence (1 minute) far surpass that generally available for long-term light curves. The data encompass two superoutbursts and 17 normal (i.e., short) outbursts. The main decay of the superoutbursts is nearly perfectly exponential, decaying at a rate ∼12 d mag −1 , while the much more rapid decays of the norm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 70 publications
(91 reference statements)
4
89
2
1
Order By: Relevance
“…Cannizzo et al (2010) reported that the fading rates of WZ Sge is much faster than the Kepler objects, V344 Lyr and V1504 Cyg, and suggested that this different could arise from the strong dependence of the viscosity in quiescence. Cannizzo et al (2010) interpreted that smaller viscosity in quiescence gives rise to a larger surface density at the start of the superoutburst and hence a steeper viscous decay. His analysis, however, used different segments between ordinary SU UMa-type dwarf novae (linearly fading part) and WZ Sge (initial rapid fading).…”
Section: Properties Of Rebrighteningsmentioning
confidence: 99%
“…Cannizzo et al (2010) reported that the fading rates of WZ Sge is much faster than the Kepler objects, V344 Lyr and V1504 Cyg, and suggested that this different could arise from the strong dependence of the viscosity in quiescence. Cannizzo et al (2010) interpreted that smaller viscosity in quiescence gives rise to a larger surface density at the start of the superoutburst and hence a steeper viscous decay. His analysis, however, used different segments between ordinary SU UMa-type dwarf novae (linearly fading part) and WZ Sge (initial rapid fading).…”
Section: Properties Of Rebrighteningsmentioning
confidence: 99%
“…Although there have been claims of other mechanisms [the enhanced mass-transfer model (Smak 1991) and pure thermal instability model (Cannizzo et al 2010)], it has been demonstrated using Kepler observations of V1504 Cyg and V344 Lyr that the TTI model is the best one to explain the observations ) (see also Osaki, Kato 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cannizzo et al (2010) studied the systematics of outbursts in V344 Lyr. Wood et al (2011) analyzed the positive and negative superhumps in the same object.…”
Section: Introductionmentioning
confidence: 99%
“…where P h is the orbital period in hr, α hot, −1 = α hot /0.1, and Cannizzo et al 2010). Cannizzo et al (2010) studied the Kepler light curves of V344 Lyr and V1504 Cyg and compared the slow fading rate during the superoutburst with other SU UMa-type dwarf novae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation